The development of geotourism and geoeducation in the Holy Cross Mountains region (central Po- land) - Gałka, Elżbieta (Quaestiones Geographicae, 2023)
The development of geotourism in the Holy Cross Mountains region has a long tradition based on the scientific and educational geological values of this area. In order to evaluate geotourism resources and their development in three representative areas of Świętokrzyskie voivodeship – the Holy Cross Mountains UNESCO Global Geopark (GGp), the central part of the Holy Cross Mountains and the Kamienna River Valley – a review of the literature and statistical data, and field studies of geosites and educational units were carried out. The Holy Cross Mountains UNESCO GGp is a first-rate geotourism region, which plays a leading role in geotourism and geoeducation, promoting geological values and infrastructure development. The central part of the Holy Cross Mountains and the Kamienna River Valley are classified as second-rate regions. The remaining areas of Świętokrzyskie voivodeship, with its unique geodiversity and biodiversity, are still waiting for their geological attractions to be discovered and shared with the broader public.